A new Approach to increasing Energy Efficiency by utilizing Cyber-Physical Energy Systems - Bornschlegl, Martin; Drechsel, Michael; Kreitlein, Sven; Bregulla, Markus; Franke, Jörg (Proceedings of the Eleventh Workshop on Intelligent Solutions in Embedded Systems (WISES) 2013, IEEE Conference Proceedings, 2013)
Cyber-Physical Systems and Industry 4.0 topics are in the focus of research. Especially energy management systems can be improved with new opportunities due to interconnected systems. Cyber-Physical Energy Systems (CPES) will help to handle the use of volatile renewable energies and to realize intelligent shut down strategies. This paper gives an overview about current CPES research topics and shows an approach, which helps to reduce the energy consumption. The main aspects are avoidance of peak loads and reduction of base load from the perspective of a car manufacturer.

A New Approach to Integrate Value Stream Analysis into a Continuous Energy Efficiency Improvement Process - Drechsel, Michael; Bornschlegl, Martin; Spreng, Simon; Bregulla, Markus; Franke, Jörg (IECON 2013. 39th annual conference on IEEE Industrial Electronics Society, 2013)
Due to increasing energy costs and the demand to lower CO2 emissions in the production, companies try to integrate a continuous energy efficiency improvement process. By implementing the energy value stream analysis, an optimized improvement process can be established which leads to a more efficient production. This approach shows a practically optimized method. It enables a holistic analysis of the energy productivity and helps to identify and to realize sustainable solutions. Furthermore this structured improvement process leads to a higher transparency of energy consumers.
Keywords: energy efﬁciency; energy management; production planning; process planning; green design; green products; energy measurement; energy value stream analysis; continuous improvement process; CIP

Holistic Approach to Reducing CO2 Emissions along the Energy-Chain (E-Chain) - Bornschlegl, Martin; Drechsel, Michael; Kreitlein, Sven; Franke, Jörg (Proceedings of the 5th International Conference (ICSAT) 2013, 2013)
Due to the increasing awareness to reduce CO2 emissions, it is important that car producers (OEM) get transparency about their energy consumption. Especially the production emission is becoming a focus topic in the next years. Hence, it should be started to minimize the energy consumption in a sustainable way. Therefore, this chapter presents a new approach to design a sustainable Energy Chain, which considers all elements beginning from the energy supplier to the end customer. Additionally the energy consumption is assessed, whether it is value-adding or not. This helps to find the levers to reduce energy consumption without reducing the level of quality and quantity. For the implementation of the Energy Chain a suitable software architecture is necessary. This chapter shows possible software modules for energy planning.